Water window ptychographic imaging with characterized coherent X-rays - Rose, Max; Skopintsev, Petr; Dzhigaev, Dmitry; Gorobtsov, Oleg; Senkbeil, Tobias; Gundlach, Andreas Robert von; Gorniak, Thomas; Shabalin, Anatoly; Viefhaus, Jens; Rosenhahn, Axel; Vartanyants, Ivan (Journal of synchrotron radiation, 2015)
A ptychographical coherent diffractive imaging experiment in the water window with focused soft X-rays at 500 eV is reported. An X-ray beam with high degree of coherence was selected for ptychography at the P04 beamline of PETRA III synchrotron radiation source. The beam coherence was measured with the newly developed non-redundant array method, and a coherence length of 4.1 µm and global degree of coherence of 35% at 100 µm exit slit opening in the vertical direction were determined. A pinhole, 2.6 µm in size, selected the coherent part of the beam that was used to obtain ptychographic reconstruction results of a lithographically manufactured test sample and a fossil diatom. The achieved resolution was 53 nm for the test sample and was only limited by the size of the detector. The diatom was imaged at a resolution better than 90 nm.